Torre de Babel e a cultura midiática - Reis, Laura Salmeron (2020)
This document aims to evaluate the existing relationships between the Tower of Babel and the media culture of the 21st century, through art, represented in the painting Torre de Babel, by Pieter Brueguel and to install Babel by Cildo Meireles, destroying the media ideal and the concept of radio key in order to understand the perpetuation of the war myth. To this end, the historical contexts of the artists in question will be analyzed, looking for interesting points between the different cultures that justify the appearance of Babel in such different moments. As a way of understanding relationships, it is necessary to enter an idea of the imaginary. Since it determines that the imaginary is a construction of social ideals together with the concept of who is the barrier of a religion with the cosmos, it becomes possible to observe that over the years a religious imaginary has been formed, which has been nurtured and strengthened, showing that Babel is part of this religious imaginary and always as a way of bringing to memory what is a fact and the same time, recalling the consequences of our choices. Babel has not disappeared from history because we remain isolated, like the Babylonians. We are always looking for the heavens, but we never recognize that we are not worthy.